Perceptions of Chinese hospital leaders on joint commission international accreditation: a qualitative study - Zhang, HongFan; Huang, Siou-Tang; Bittle, Mark J.; Engineer, Lilly; Chiu, Herng-Chia (Frontiers in Public Health, 2023)
Background Joint Commission International (JCI) accreditation plays a significant role in improving the quality of care and patient safety worldwide. Hospital leadership is critical in making international accreditation happen with successful implementation. Little is known about how Chinese hospital leaders experienced and perceived the impact of JCI accreditation. This paper is the first study to explore the perceptions of hospital leaders toward JCI accreditation in China. Methods Qualitative semi-structured interviews were used to explore the perceptions of the chief operating officers, the chief medical officers, and the chief quality officers in five JCI-accredited hospitals in China. Thematic analysis was used to analyze the interview transcripts and identify the main themes. Results Fifteen hospital leaders participated in the interviews. Three themes emerged from the analysis, namely the motivations, challenges, and benefits related to pursuing and implementing JCI accreditation. The qualitative study found that eight factors influenced hospital leadership to pursue JCI accreditation, five challenges were identified with implementing JCI standards, and eight benefits emerged from the leadership perspective. Conclusion Pursuing JCI accreditation is a discretionary decision by the hospital leadership. Participants were motivated by prevalent perceptions that JCI requirements would be used as a management tool to improve the quality of care and patient safety in their hospitals. These same organizational leaders identified challenges associated with implementing and sustaining JCI accreditation. The significant challenges were a clear understanding of the foreign accreditation standards, making staff actively participate in JCI processes, and changing staff behaviors accordingly. The top 5 perceived benefits to JCI accreditation from the leaders’ perspective were improved leadership and hospital safety, improvements in the care processes, and the quality of care and the learning culture improved. Other perceived benefits include enhanced reputation, better cost containment, and a sense of pride in the staff in JCI-accredited hospitals.